Technical Progress and Structural Change in the Swedish Cement Industry 1955-1979 - Forsund, Finn R.; Hjalmarsson, Lennart (Econometrica, 1983)
The purpose of this article is to provide a deeper empirical insight into the structural change of an industry which is more relevant than that obtained by an analysis based on the traditionally estimated average production function. The main contribution is a long run analysis of technical progress and structural change by means of the short run industry production function introduced by Johansen [13], and based on micro data for individual production units. For that purpose we have developed Johansen’s approach into an operational framework for discrete capacity distributions including a special algorithm for the computation of the short-run industry production function. (This abstract was borrowed from another version of this item.)